Circadian rhythm disorders in patients with advanced cancer: a scoping review - Gouldthorpe, Craig; Power, Jenny; Davies, Andrew (Frontiers in Oncology, 2023)
Circadian rhythms describe patterns which occur roughly every 24-hours, including patterns of sleep and wake, rest and physical activity, and changes in blood melatonin and cortisol levels. Regular and strong patterns can become abnormal in patients with cancer and may be associated with a worse outcome. This review aimed to assess how circadian rhythms are investigated, what the circadian rhythms and abnormal rhythms are, and what impact this may have on patients with advanced cancer. The review highlighted that several approaches have been used investigate and report circadian rhythms in this patient group. Despite this, abnormal circadian rhythms appear to be common in patients with advanced cancer and are associated with increased symptoms, poorer quality of life and shorter survival. Several gaps in the evidence have been highlighted and areas for future research highlighted.